Model Kepemimpinan Berbasis Nilai Islam dalam Menanggapi Tantangan Keorganisasian Pendidikan Abad 21 di Ma'had Tahfidz Tafaqquh, Kampar, Riau : Penelitian - Abdul Wahid Wandana; Ardyanto Ardyanto; Ahmad Bayhaqi; Sofwan Manaf; Busthomi Ibrohim (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to explore the model of leadership based on Islamic values in responding to the organizational challenges of 21st-century education at Ma'had Tahfidz Tafaqquh, Kampar, Riau. Using a qualitative case study approach, the research collected data through semi-structured interviews, participatory observation, and documentation. The participants included leaders, educators, and senior students involved in decision-making and policy implementation at the institution. The data analysis revealed three main themes: (1) transformative leadership based on Islamic values focusing on character development and 21st-century skills, (2) managing changes and educational challenges by integrating technology while maintaining Islamic principles, and (3) the role of the community in creating an adaptive learning environment. These findings contribute to the understanding of how Islamic values-based leadership can be adapted to address modern educational challenges and provide practical guidance for other Islamic educational institutions. In conclusion, this study has significant implications for the development of Islamic education leadership theory and offers insights for designing policies that support the integration of Islamic values with educational technology.